All Signs Point to Cancer: A Case of Cryptic Miliary Tuberculosis in the Setting of Concomitant Cancer - Victoria Cress; Sue Min Sophia Kwon; Michael T. Ulrich (Case Reports in Infectious Diseases)
Dissemination of tuberculosis (TB) is known as miliary tuberculosis. When miliary tuberculosis lacks classic radiographic and clinical features, it can be labeled cryptic miliary tuberculosis and may mimic metastatic cancer. This unusual presentation of an already atypical form of TB often delays diagnosis. We present a case of a 58-year-old female who presented with presumed metastatic carcinoma, who was ultimately diagnosed with both primary breast cancer and disseminated TB. This case emphasizes the need for a high index of suspicion for miliary tuberculosis in patients with presumed or proven malignancy.